Part A

(1) A =

(1 − 1/n, 1 + 1/n) = {1}
n=1

Bounded both above and below. Ans (c). (2) B={r ∈ Q : r2 < 2} sup B = Ans.(d) (3)Direct consequence of lemma 32.2 in text book. Ans.(c) √ √ 2, inf B = − 2 hence No rational supremum or infimum.

Part B (1) xn −→ x, xn −→ y Let x = y Then |x − y| > 0, and let |x − y| = . For this ∃ integer N1 such that |x − y| < /3 n > N1 (1 Mark) (1 Mark)

and ∃ integer N2 such that |x − y| < /3 Let N= max{N1 , N2 }, n > N

n > N2

⇒ |xn − x| < /3 and |yn − y| < /3.

But |x − y| ≤ |xn − x| + |xn − y| < 2 /3. a contradiction. Therefore x = y (2 Marks)

[1 Mark each for the correct interpretation of xn −→ x, and xn −→ y, and 2 Marks for the final answer.] 1

(1 Mark) As f is decreasing on [n. n + 1]. x2 such that a < x1 < x2 < b ∀ x (a.b).] (3) f : R −→ [0. and so f (t) ≥ f (n + 1) f (n + 1) − f ≤ 0 and so n+1 (f (n n + 1) − f )dt ≤ 0 2 .(2) (a) f: (a. x2 were arbitrary and so f is strictly increasing on (a.b) such that f (x2 ) − f (x1 )/x2 − x1 = f (x) > 0 (2 Marks) Since x2 − x1 > 0. (b) 1 Mark for replying “NO”.b). 1 Mark for justifying the example. n + 1]. + f (n) − n+1 1 n 1 f (t)dt n+1 n an+1 − an = f (n + 1) − = = n+1 n f dt + n 1 f dt = f (n + 1) − (1 Mark) f dt f (n + 1)dt − n+1 n f dt n+1 (f (n n + 1) − f )dt ∀ t [n. and 1 Mark for the correct deduction.b)−→ R is differentiable and f (x) > 0 x1 .. (b) No. f (x2 ) − f (x1 ) > 0 and f (x2 ) > f (x1 ) (1 Mark) x1 .1)−→ R .. ∞) is a decreasing function and hence Riemann integrable on any interval . f (x) need not be positive f: (-1. f (x) = x3 (1 Mark) (1 Mark) (1 Mark) f is strictly increasing but f (0) = 0 [(a) 2 Marks for the correct use of the mean value theorem. Consider By Mean value theorem ∃ x (a. 1 Mark for the correct counterexample. (a) an = f (1) + f (2) + .

(1 Mark). 1 Mark for proper justification f (i)−f ≥ 0 on [i. 1 Mark for proper justification f (n + 1) − f ≤ 0 and so n+1 (f (n n + 1) − f )dt ≤ 0. (c) 2 Marks for observing that the sequence is decreasing and bounded below.] 3 . (2 Marks) [(a) 1 mark for correct expansion.. i + 1] and so i+1 (f (i) i − f )dt ≤ 0.. (b) 1 mark for correct expansion. and 1 Mark for the final answer.. and 1 Mark for the final answer. Therefore an ≥ 0 (1 Mark) (c) {an } is a decreasing sequence and is bounded below by 0. 1 Mark for concluding that it should then be convergent.. i + 1]. therefore an converges in R.Therefore an+1 ≤ an (1 Mark) (b) 3 2 an = f (1) + f (2) + . + f (n) − n n−1 n 1 f (t)dt = 2 1 f (1)dt − 2 1 f (t)dt + 3 2 f (t)dt − f (t)dt + . + i−1 (f (i) i f (n − 1)dt − n n−1 f (t)dt + f (n) (1 Mark) =Σn−1 i=1 − f )dt + f (n) (1 Mark) Since f (i) − f ≥ 0 on [i.